Buttons and bones [large type] - Ferris, Monica (Ferris, Monica. Needlecraft mystery., 2011)
While renovating a cabin in the Minnesota woods, Betsy Devonshire, owner of the Crewel World needlework shop, discovers the skeleton of a Nazi. Her investigation yields the site of a former German POW camp and an intricately designed pattern of clues to a decades-old crime.